Salivary Osteocalcin as Potential Diagnostic Marker of Periodontal Bone Destruction among Smokers - Joseph, Betsy (Biomolecules, 2020)
The objective of the study was to assess the levels and diagnostic accuracy of salivary osteocalcin (OC), osteonectin (ON), and deoxypyridinoline-containing degradation fragment of the C-terminal telopeptide region of type I collagen (CTX) in adult smokers with periodontal bone destruction. Towards this, ninety systemically healthy patients (groups I: healthy, II: periodontitis with non-smokers, and III: periodontitis with current smokers) were included in the study. The results showed a positive correlation (weak to moderate) was observed for OC, ON, and CTX with probing pocket depth (PPD; r = 0.40, 0.32, and 0.36) and alveolar bone loss (BL; r = 0.58, 0.38, and 0.51) (p < 0.01). Smoker periodontitis was best discriminated from healthy controls using 15.25 ng/mL of OC (AUC: 0.870; 95% CI: 0.757–0.943; YI (Youden Index): 0.693; p < 0.0001). However, with a cut-off of BL at 33.33%, 19.24 ng/mL of salivary OC gave the best discrimination (AUC: 0.809; 95% CI: 0.686–0.900; Se: 80.0%; Sp: 73.47%, and YI: 0.534). A 16.45 ng/mL amount of OC gave excellent discrimination (AUC: 0.811; 95% CI: 0.688–0.901; Se: 92.31%; Sp: 65.22%, and YI: 0.575) among healthy and smoker periodontitis when PD at 6mm was considered as cut-off. Conclusion: The best discrimination between healthy controls and smoker periodontitis was obtained at 15.25 ng/mL of salivary OC.